VAN WYK-GRUMBACH SYNDROME: A CHILD WITH MENSTRUATION - Mathews, Gerard Jason; Yee, Teh When; Subramaniam, Seetha Devi; Mathews, Joel; Merican, Nor Shaffinaz Yusoff Azmi; Abdullah, Noor Rafhati Adyani; Ismail, Shartiyah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Van Wyk-Grumbach Syndrome (VWGS) is a rare presentation of severe untreated hypothyroidism. Classically, it presents with isosexual pseudopuberty, enlarged multicystic ovaries and delayed bone age. CASE We report a case of a 10-year-old female who presented to our department with weight gain and severe anaemia (Hb 4.2 g/dL) secondary to menorrhagia. Further history revealed she attained menarche at the age of 8. Her Tanner staging at presentation was B3 and P1. She was obese and short with a height of 127 cm (below 3rd centile). She lacked pubic hair, with short stature and delayed bone age which differentiated her from the usual presentation of central precocious puberty. Abdominal ultrasonography revealed bulky uterus with multicystic ovaries. Blood investigations revealed TSH 91.6 mIU/L, T4 12.92 pmol/L, LH 4.6IU/L, FSH 5.1IU /L, estradiol (E2) 984.4 pmol/L. Thyroid peroxidase antibodies were elevated. Therefore, she was diagnosed with severe autoimmune hypothyroidism with precocious puberty. She was treated with L-thyroxine 100 mcg daily. GnRH Agonist (Leuprorelin) was initiated for a total of 18 months to halt premature puberty and to achieve age-appropriate target height. CONCLUSION Sexual precocity in a short, obese child with delayed bone age is a harbinger of VWGS. High TSH levels act through FSH receptors inducing an FSH like effect causing the prepubertal response seen in VWGS. Early puberty accelerates growth and promotes bone maturation, leading to early fusions that cause a decrease in final adult height (FAH). In our case, Leuprorelin was used to suppress the secretion of sex hormones, inhibit rapid bone maturation, and prolong the growth period, which improved FAH. This case highlights the importance of recognizing VWGS, so that thyroxine treatment can be initiated.